PELATIHAN HARGA POKOK PRODUKSI OLEH PT PLN UIP SUMBAGSEL DALAM MENDUKUNG PENGEMBANGAN UMKM DI DESA AIR SEMPIANG KABUPATEN KEPAHIANG PROVINSI BENGKULU - Kholek, Abdul; Putri, Nurilla Elysa; Nasyaya, Annada; Simarmata, Marudut J.F.; Anugrah, Erwin C; Pahira, Lira; Zalyanti, Detia; Akbar, Dinar Tri (LP2M STP Mataram, 2024)
MSMEs Putri Land Bouw, located in Air Sempiang Village, Kepahiang Regency, Bengkulu Province, is one of the beneficiaries of the TJSL (Social and Environmental Responsibility) Program initiated by PT PLN (Persero) UIP Sumbagsel in fulfilling its commitment to encourage and be involved in the advancement of Micro and Small Enterprises. and Medium to become more advanced and independent creative economic businesses. Training is a form of initial encouragement which is quite important in providing information, education and discussion forums. MSMEs often do not take into account production costs which can result in the company's selling price being set too high or too low. In this case, the TJSL program for Putri Land Bouw MSMEs was carried out by providing training on cost of production. The training was carried out using seminar, discussion, practice and post test methods, all of which were aimed at deepening understanding of the production costs of Putri Land Bouw MSMEs. The result of these two trainings was that the training participants were able to understand the material presented by the resource person well. One of the ways this is proven is the increase in knowledge between before and after training which can be seen from the results of the practice of determining Cost of Goods Production in groups and the results of the existing post-test average scores. Participants were also active in practice, questions and answers and discussions